2019
DOI: 10.1007/s40472-019-0231-3
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and Long-Term Post-Kidney Transplant Outcomes

Abstract: Purpose of review: To highlight recent research about frailty and its role as a predictor of adverse, long-term post-kidney transplant (KT) outcomes. Recent findings: Frailty is easily measured using the physical frailty phenotype (PFP) developed by gerontologist Dr. Linda Fried and colleagues. In recent studies, >50% of KT recipients were frail (20%) or intermediately frail (32%) at KT admission. Frail recipients were at 1.3-times higher risk of immunosuppression intolerance and 2.2-times higher risk of morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 66 publications
2
33
0
1
Order By: Relevance
“…Additionally, prior studies have demonstrated the dynamic nature of frailty among ESKD patients undergoing HD, on the waitlist, or recipients post-KT, such that improvements in frailty scores can be observed over time [39-41]. This suggests that frailty in many cases is not an irreversible state of low physiological reserve [41, 42], which provides an optimistic avenue for intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, prior studies have demonstrated the dynamic nature of frailty among ESKD patients undergoing HD, on the waitlist, or recipients post-KT, such that improvements in frailty scores can be observed over time [39-41]. This suggests that frailty in many cases is not an irreversible state of low physiological reserve [41, 42], which provides an optimistic avenue for intervention.…”
Section: Discussionmentioning
confidence: 99%
“…44 A growing body of evidence describing the importance of measuring frailty in KT candidates is emerging and has previously been reviewed. 45,46 At the time of KT, 20% of patients are defined as frail according to the PFP. 47 Frailty has been associated with adverse outcomes before and after KT (Figure 2).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…[91][92][93][94] Another aging process implicated in the pathogenesis of frailty is cellular senescence. 46,95 Cellular senescence is a state of essentially irreversible growth arrest that occurs in response to perturbations such as DNA damage and oxidative stress.…”
Section: Mechanisms Of Frailtymentioning
confidence: 99%
“…Specifically, the combination of comorbidities, sarcopenia, and uremia‐associated inflammation contributes to the development of frailty and decreased functional status in many patients 4‐6 . Frailty is commonly defined as a syndrome of multi‐system physiologic dysfunction which leads to decreased ability to recover from adverse medical events 7 . Decreased functional status refers to challenges performing activities of daily living.…”
Section: Introductionmentioning
confidence: 99%